Response of Water Environment to Land Reclamation in Jiaozhou Bay, China Over the Last 150 Years - Xu, Chunyang; Zhou, Chunyan; Ma, Kao; Wang, Peng; Yue, Xihe (Frontiers in Marine Science, 2021)
Jiaozhou Bay (JZB), located at Qingdao City, northern of China, is a semi-enclosed shallow bay that has undergone large-scale land reclamation and is suffering deteriorated water environment. Long-term evolution of JZB with respect of coastline, tidal prism, tidal dynamics, water-exchange capacity and pollutant transport from 1863 to 2020 was investigated in this paper, on the basis of remote sensing images, historical charts and numerical model. The JZB was predominated by natural evolution from 1863 to 1935, during which the coastline barely changed. Thereafter, human intervention became intense and more and more natural tidal flats were replaced by salt pond, aquaculture area, and reclamation very quickly. As a result, tidal prism, area of tidal flats, area of JZB decreased sharply by 0.290 km3, 182 km2, 223 km2 respectively from 1935 to 2020, corresponding to annual decreasing rate being of 123 times, 10 times, 12 times respectively as that of before 1935. Numerical model showed that the residual current in JZB tended to be weaker due to the change of coastline and bathymetry, which is not favoring the water-exchange and pollutant transport, especially in the northeast of JZB. The basin residence time increased from 15.5 days in 1935 to 17.6 days in 2020, because of weaker residual tidal current and smaller tidal prism. Local residence time increased significantly near the area with large land reclamation, especially in the northeast and west of JZB. Distribution of dissolved inorganic nitrogen (DIN), in each year, which is the dominant pollutant in JZB, indicated higher DIN concentration and weaker transport along with reclamation. The research on JZB evolution over the last 150 years can provide useful suggestions for the decision-makers of the local government to improve the marine ecosystem. The systematic method to investigate long-term water environment evolution of JZB can be referred to study other semi-closed bays.